Teacher Learning Strategies in Improving the Ability to Read the Qur'an Using the Ummi Method - Lilik Masruroh; Abdillah Syamlan (Global Education Journal, 2026)
The ability to read the Qur'an tartil according to the rules of tajweed is a basic competency in tahfidz education, but there are still obstacles in the fluency, accuracy of reading, and variety of students' abilities that require effective learning strategies. At the Markaz Tahfidz Ar-Riyadh Bangil, learning uses the Ummi Method, but its implementation still faces several obstacles. The purpose of this study is to examine the application of teacher learning strategies based on the Ummi Method in improving students' Qur'an reading ability and analyze its supporting and inhibiting factors. This research method uses a descriptive qualitative approach carried out at Markaz Tahfidz Ar-Riyadh Bangil with the researcher as the main instrument. Data was obtained through participatory observation, semi-structured interviews with ustadz and managers, and documentation, then analyzed using the Miles and Huberman interactive model which included data reduction, data presentation, and conclusion drawn. The validity of the data is tested through source triangulation, technical triangulation, and member check. The results of the study show that the teacher's learning strategy based on the Ummi Method at Markaz Tahfidz Ar-Riyadh Bangil is carried out through systematic planning, the application of talaqqi and musyafahah, muraja'ah habituation, and consistent gradual evaluation. This strategy is effective in increasing the fluency, accuracy of tajweed, and the confidence of students in reading the Qur'an. Supporting factors include ustadz's commitment, structured learning system, and institutional support, while inhibiting factors include differences in students' abilities, limited time, and lack of concentration and motivation to learn.